Urbanization and land surface temperature dynamics in Bahir Dar, Ethiopia: a comparative analysis of pre- and post-capital status - Melese, Mastawal; Anteneh, Mesfin; Bantigegn, Simachew (Frontiers in Environmental Science, 2025)
Introduction: Rapid urbanization alters Land Use Land Cover (LULC) patterns, affecting Land Surface Temperature (LST) and intensifying the Urban Heat Island (UHI) effect. However, few studies have examined the long-term thermal impacts of urban expansion, particularly pre- and post-capital designation effects in rapidly growing cities like Bahir Dar, Ethiopia.Methods: This study analyzes LULC changes and LST dynamics from 1984 to 2024 using remote sensing and geospatial techniques. Supervised classification with the maximum likelihood algorithm was applied to Landsat imagery to classify LULC into five categories. LST was retrieved from thermal infrared bands and analyzed with the normalized difference vegetation index (NDVI), built-up index (NDBI), and modified normalized difference water index (MNDWI) to assess urban heat variations.Results: The findings reveal a 366% expansion of built-up areas, along with a 26.8% decline in agricultural land and a 34.2% decrease in wetlands. Before 1994, vegetation and wetlands moderated LST, with an LST-NDVI correlation of −0.069 (1984), which weakened to −0.0549 (2024). The LST-MNDWI correlation dropped from −0.1409 to −0.0588, while LST-NDBI shifted from 0.0831 to 0.0235.Discussion: These results highlight the need for climate-sensitive urban planning. Expanding green infrastructure, restoring wetlands, and adopting climate-adaptive policies are crucial for managing UHI effects in rapidly urbanizing cities. This study offers insights for policymakers and urban planners to enhance climate resilience in Bahir Dar and similar cities.